Pengaruh Modal Intelektual terhadap Kinerja Keuangan pada Sektor Perbankan - Indriyana Puspitosari (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2016)
The principal purpose of this study is to investigate the influence of the three components of intellectual capital: physical capital (VACA), human capital (VAHU), and structural capital (STVA) toward ROA as the proxy of financial performance on listed banking industry from 2012-2014. Empirical analysis is conducted using linear multiple regression analysis which is ROA as dependent variable, the intellectual capital component as independent variables and firm size as control variable. From the empirical analysis using sample of 23 listed banking industry indicates that the three components of intellectual capital have positive significant effect on ROA, and physical capital is the strongest predictor.